Fuzzy expert systems (FES) for halal food additive - M. Zaki Zakaria; Norhana Nordin; Ariff Md Ab Malik; Shamsul J Elias; Ahmad Zambri Shahuddin (Institute of Advanced Engineering and Science, 2019)
Halalan Toyyiban issues acknowledged the need of additional protection for good quality assurance food and should be applied in the food industries. All the food ingredients must be safe, hygiene and nutritious to be used by the consumers. Many chemical ingredients have been added in the food production process in enhancing the food characteristics and act as stabilizer, artificial colour, preservatives, artificial sweetener. This paper presents Halal Food Additive Using Fuzzy Expert Systems (FES) to determine the Halalan Toyyiban safety rating for food additives based on consumers’ past experienced record in allergy complication. The significant of this project is to provide the consumers with health awareness to prevent the health risk that caused by these food additives. This research focuses on 42 types of Halal food additives and 12 type symptoms of allergies that are commonly faced by the consumers.